2020
DOI: 10.20473/jmv.vol3.iss1.2020.76-81
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Ekstrak Dandang Gendis (Clinacanthus nutans) Terhadap Kadar Glukosa Darah pada Tikus Wistar Model Diabetes Melitus

Abstract: Diabetes Melitus adalah penyakit yang ditandai dengan hiperglikemia karena sekresi insulin yang sedikit, aksi insulin kurang poten, atau disebabkan keduanya. Daun dandang gendis (Clinacanthus nutans)diketahui mengandung antioksidan yang dilaporkan mampu menurunkan kadar glukosa darah. Penelitian ini untuk mengetahui pengaruh pemberian ekstrak daun dandang gendis terhadap kadar glukosa darah pada tikus Wistar model diabetes. Tikus sebanyak 30 ekoryang sesuai kriteria dibagi dalam 5 kelompok yang kemudian diindu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Previous research by Dewinta et al in 2020 that the administration of ethanol extract of dandang gendis leaves (Clinacanthus nutans) has potential as an antidiabetic by lowering blood sugar levels in diabetic white Wistar rats. This is because the leaves of dandang gendis (Clinacanthus nutans) contain flavonoids and fatty acids as antioxidants that can lower blood sugar levels (Dewinta et al, 2020). Another research conducted by Panggabean et al in 2014 examined the "Activity Test of Increasing Insulin Sensitivity of Black Cumin Seed Extract (Nigella sativa) Through Measurement of Tyrosine Concentration Phosphorylated Insulin Receptor Substrate-1 (IRS-1)" that the administration of black cumin extract which has various contents, one of which is palmitic acid can increase insulin sensitivity and lower blood glucose levels.…”
Section: Ligand-receptor Molecular Docking Test Resultsmentioning
confidence: 99%
“…Previous research by Dewinta et al in 2020 that the administration of ethanol extract of dandang gendis leaves (Clinacanthus nutans) has potential as an antidiabetic by lowering blood sugar levels in diabetic white Wistar rats. This is because the leaves of dandang gendis (Clinacanthus nutans) contain flavonoids and fatty acids as antioxidants that can lower blood sugar levels (Dewinta et al, 2020). Another research conducted by Panggabean et al in 2014 examined the "Activity Test of Increasing Insulin Sensitivity of Black Cumin Seed Extract (Nigella sativa) Through Measurement of Tyrosine Concentration Phosphorylated Insulin Receptor Substrate-1 (IRS-1)" that the administration of black cumin extract which has various contents, one of which is palmitic acid can increase insulin sensitivity and lower blood glucose levels.…”
Section: Ligand-receptor Molecular Docking Test Resultsmentioning
confidence: 99%
“…Groups V, VI, and VII were given belalai gajah plants extract at doses of 75 mg/kg body weight, 150 mg/kg body weight, and 300 mg/kg body weight. The dose of belalai gajah plants extract refers to Dewinta et al (2020) 42 and diuretic testing following the Cumming method. 49 Mice were fasted for ± 18 hours, then their body weight was weighed.…”
Section: Testing the Diuretic Activity Of Belalai Gajah Plantsmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41] Previous studies have shown that giving (belalai gajah plants) plants at a dose of 75 mg/kg body weight can significantly reduce blood glucose levels in diabetic rats. 42 Previously it was reported that administration of aqueous extract of belalai gajah plants at a dose of 150 mg/kg body weight resulted in a decrease in blood glucose levels in diabetic mice by alloxan induction. 43 In addition, it was also reported that administration of aqueous extract of belalai gajah plants at a dose of 75 mg/kg BW was effective in reducing blood glucose levels in diabetic rats.…”
mentioning
confidence: 99%
“…Three days after induction, the rats were checked for blood glucose levels using a glucometer. The rats were declared to have diabetes if their blood glucose levels were ≥200 mg/dL and were called the diabetic rat model [18,[26][27][28].…”
Section: Animal Modelsmentioning
confidence: 99%